(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: The present study was aimed at the molecular detection of HBV infection among patients with chronic liver disease (CLD) and to study the mutation spectrum S-gene region in the occult HBV strains. Materials and Methods: An observational study conducted on 200 clinically diagnosed CLD cases enrolled from the Gastroenterology unit. Two hundred serum samples were screened with Fibroscan and for HBsAg, HBCT and estimated liver enzymes. Samples positive for either HBsAg or Anti HBc total were further evaluated for other HBV markers and presence of HBV DNA. The S region was amplified in occult CHB cases and sequenced. Results: 70.5% (141) of the patients with CLD were suffering with Chronic Hepatitis B virus (CHB). The HBV DNA was detected in 19.14% patients. Four cases were in occult phase. Two samples of them could be amplified. The isolates belong to the genotype A, and revealed certain mutations leading to novel amino acids. Conclusions: Mutations in the S gene sequences of HBV virus from the Occult HBV infection (OBI) patients would lead to immune escape or cause occult infection. In the Genotype A at two positions, amino acids that are likely to cause occult infection are observed apart from mutations at certain positions leading to novel amino acids.